When on the mountain top, create new summits, says Samsung Asia Pacific CEO - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
The past couple of years have been nothing short of phenomenal for Korean electronics giant, Samsung. The company has seen success with a number of their products, particularly in the television business. "For TV, we've been number one in the world since 2005," exclaimed Gregory Lee, President and CEO of Samsung Asia.